INDEKS PERAN PENYULUH AGAMA DALAM MEMBINA KEHIDUPAN BERAGAMA KELUARGA MAJELIS TAKLIM DI KABUPATEN SRAGEN JAWA TENGAH Index of The Roles of Religion Extension Agent on Guiding Religious Life for Majlis Taklim in Sragen District Central Java - Rosidin Rosidin (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Religion advisor for a family is a starting point in the success of nation building. This essay is to explore the quality index of religion advisor in conducting family guiding through religious gathering. This study uses a quantitative approach. From the validity and reliability test it can be seen that 32 items are valid and reliable. There are 107 samples, these respondents are selected using purposive random sampling. Results of this research show; firstly index of the roles of religion advisors in guiding Majlis Taklim family stands at 78.71 or good. Secondly, The aspect of religion advisor that are studied including communication capacity, service quality, and attitude of religion advisor are categorized as very good. but the participation of religion advisor is categorized as not good, it means that is not fulfill the consumers’ expectation. Thirdly, the least score of religion’s advisor is participation element which stands at 58.06 (not good), therefore this needs to be developed.